Dynamic evolution of interface roughness during friction and wear processes. Issue 1 (25th February 2013) - Kubiak, K.J.; Bigerelle, M.; Mathia, T.G.; Dubois, A.; Dubar, L.; Brown, Christopher A.
Summary Dynamic evolution of surface roughness and influence of initial roughness (Sa = 0.282–6.73 µm) during friction and wear processes has been analyzed experimentally. The mirror polished and rough surfaces (28 samples in total) have been prepared by surface polishing on Ti–6Al–4V and AISI 1045 samples. Friction and wear have been tested in classical sphere/plane configuration using linear reciprocating tribometer with very small displacement from 130 to 200 µm. After an initial period of rapid degradation, dynamic evolution of surface roughness converges to certain level specific to a given tribosystem. However, roughness at such dynamic interface is still increasing and analysis of initial roughness influence revealed that to certain extent, a rheology effect of interface can be observed and dynamic evolution of roughness will depend on initial condition and history of interface roughness evolution. Multiscale analysis shows that morphology created in wear process is composed from nano, micro, and macro scale roughness. Therefore, mechanical parts working under very severe contact conditions, like rotor/blade contact, screws, clutch, etc. with poor initial surface finishing are susceptible to have much shorter lifetime than a quality finished parts. SCANNING 36:30–38, 2014. © 2013 Wiley Periodicals, Inc.